Determination of the Incidence and Prevalence Rates of Chronic Diseases among Old age at Al-Russafa District in Baghdad City - Essra Ibrahim Khudair, Mohammed F. Khalifa (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To evaluate the incidence and prevalence rates of chronic diseases among old age at Al-Russafa District in Baghdad City. Methodology: A descriptive design, using the evaluation approach, is employed to determine of the incidence and prevalence rates of chronic diseases among old age at al-Russafa District in Baghdad City from October10th 2021 to April 2nd 2022. A non-probability, convenient sample of (672214) old age, is selected for the purpose of the study. All subjects have signed consent form to present their agreement for participation in the study. The confidentiality of the data is also safeguard and they will be securely maintained during and after conducting the study. A questionnaire is constructed for the purpose of the study through review of related literature. It is consisted of (3) main parts; old age demographic characteristics, old age chronic diseases and the incidence and the prevalence of old age chronic diseases. Content validity is determined for the study instrument through panel of experts and internal consistency reliability is obtained for the study instrument through split-half technique and the computation of Cronbach alpha correlation coefficient in a pilot study. Data are gathered through the use of the study instrument as mean of data collection and analyzed through the application of descriptive statistical data analysis and inferential statistical data analysis approaches. Results: The study results depict that old age chronic diseases are accounted for cardiovascular and chronic respiratory diseases at Al-Russafa District in Baghdad City. Males old age have been prominently at greater risk to the incidence and the prevalence of such diseases more than females at Al-Russafa District in Baghdad City. Conclusion: The study concludes that high incidence rates are accounted for chronic respiratory diseases, cardiovascular diseases, arterial hypertension, kidney diseases, diabetes mellitus and arthritis at Al-Russafa District in Baghdad City and high prevalence rates are accounted for chronic respiratory diseases, cardiovascular diseases, arterial hypertension, kidney diseases and diabetes mellitus at Al-Russafa District in Baghdad City. Recommendations: The study recommends that screening and early detection programs should be planned and implemented on regular base for the finding of such subpopulation-based health problems. Further and nation-wide research can be conducted on large scale sample size and different settings.